Plastic collapse load prediction of cracked circular hollow section T/Y-joints under in-plane and out-of-plane bending. (15th January 2018) - Li, Tao; Lie, Seng-Tjhen; Shao, Yong-Bo
Abstract: The plastic collapse loads of cracked circular hollow section (CHS) T/Y-joints under in-plane and out-of-plane bending are investigated using finite element (FE) analyses. An in-house 3D FE mesh generator is specifically developed to create the mesh models of the cracked joints containing a semi-elliptical surface crack located at the weld toe of the chord. Mesh convergence tests are then carried out to check the accuracy of the generated mesh models. The in-plane and out-of-plane plastic collapse moments of uncracked CHS T/Y-joints are calculated and compared with results obtained from three codes and experimental data. The comparison shows that the plastic collapse moments of uncracked CHS T/Y-joints obtained in this study are accurate and reliable. Subsequently, an extensive parametric study is carried out to investigate the plastic collapse moments of cracked CHS T/Y-joints under in-plane and out-of-plane bending. It is found that the in-plane and out-of-plane plastic collapse moments may decrease by up to 35.1% and 33.6% respectively when the crack area A nc reaches 25% of the intersectional area, t 0 * l w . Finally, two lower bound strength reduction factor F AR equations for cracked CHS T/Y-joints under in-plane and out-of-plane bending are proposed. Highlights: Develop a generator to create FE mesh models of cracked CHS T/Y-joints containing a surface crack. Provide various mesh refinement schemes in the in-house mesh generator. Investigate the plastic collapse moments of cracked CHS T/Y-joints under in-plane and out-of-plane bending. Crack area has the most significant influence on the plastic collapse moments of cracked CHS T/Y-joints. Propose two lower bound strength reduction factor equations.